FOREIGN LANGUAGE ANXIETY IN ADOLESCENCE - Sucipermata, Rd. Jeny (2017)
This paper entitled "Foreign Language Anxiety in Adolescence" is aimed at examining the anxiety level experienced by adolescents students, to find out the factors of their anxiety and to investigate their coping strategies in foreign language anxiety. The participants of this study were 34 of 9th graders students from one Junior High School in Bandung. Data were collected through classroom observation which took place twice, distributing questionnaires and conducting semi-structure interview with selected students. This research used descriptive qualitative design, while, the data collected were analyzed using Foreign Language Classroom Anxiety Scale (FLCAS) proposed by Horwitz et al (1986).,. According to the result of data analysis, it was found that there were 23 out of 34 students experienced language anxiety, 26% high anxiety, 67.65% moderate anxiety and 5.88% low anxiety. However, in order to have a further understanding of the students' foreign language anxiety, 6 anxious students (high, mid and low level of anxiety) were selected as the respondents to be interviewed. As a result, it was found that the most common factor of students' language anxiety is communication apprehension. Moreover, to overcome the anxiety, the most common coping strategies used by the respondents (5 out of 6 respondents) of this study was the flight behaviors such as avoidance or withdrawal. ;---Skripsi ini berjudul "Foreign Language Anxiety in Adolescence" yang bertujuan untuk memeriksa tingkat kecemasan yang dialami oleh siswa remaja, untuk mengetahui faktor-faktor kecemasan mereka dan untuk menyelidiki strategi untuk mengatasi kecemasan berbahasa asing. Peserta didik dari studi ini berjumlah 34 orang siswa dari kelas 9 sekolah menengah pertama di Bandung. Data dikumpulkan melalui observasi kelas yang dilakukan dua kali, mendistribusikan kuesioner, dan melakukan wawancara dengan siswa. Penelitian ini menggunakan desain kualitatif deskriptif, sementara itu, data yang dikumpulkan akan dianalisis menggunakan Foreign Language Classroom Anxiety Scale (FLCAS) oleh Horwitz et al (1986).,. Sesuai dengan hasil analisis data, ditemukan bahwa ada 23 dari 34 siswa mengalami kecemasan dalam berbahasa asing, 26% untuk high anxiety, 67.65% untuk moderate anxiety dan 5,88 low anxiety. Namun, untuk memiliki pemahaman yang lebih lanjut, 6 siswa anxious (high, mid dan low level of anxiety) dipilih sebagai responden untuk diwawancarai. Hasilnya ditemukan bahwa faktor yang paling umum pada siswa yang mempunyai kecemasan dalam berbahasa adalah ketakutan dalam berkomunikasi. Selain itu, untuk mengatasi kecemasan yang dialami oleh siswa, strategi yang paling umum digunakan oleh responden (5 dari 6 responden) dari studi ini adalah flight behaviors seperti avoidance atau withdrawal.